Changepoints of annual flood-layer from sediment core POS362-2_33 - Cécile L Blanchet; Arne Ramisch; Rik Tjallingii; Monica Ionita; Louison Laruelle; Bagge Meike; Volker Klemann; Achim Brauer (PANGAEA, 2024)
The dataset provides information about changepoints identified in the sediment accumulation rate profile of marine core POS362_2_33. The study site is located on the Nile deep-sea fan and the core was collected in 2008. Using annual layer thickness determination (see doi:10.1594/PANGAEA.967743), sediment accumulation rates were calculated and eight changepoints were detected. We report here the depth and age of each changepoints and the number and average thickness of flood-layers between each changepoint. Further details can be found in the related